2009
DOI: 10.1086/605953
|View full text |Cite
|
Sign up to set email alerts
|

Jettisoning Ballast or Fuel? Caudal Autotomy and Locomotory Energetics of the Cape Dwarf GeckoLygodactylus capensis(Gekkonidae)

Abstract: Many lizard species will shed their tail as a defensive response (e.g., to escape a putative predator or aggressive conspecific). This caudal autotomy incurs a number of costs as a result of loss of the tail itself, loss of resources (i.e., stored in the tail or due to the cost of regeneration), and altered behavior. Few studies have examined the metabolic costs of caudal autotomy. A previous study demonstrated that geckos can move faster after tail loss as a result of reduced weight or friction with the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…(2) I recorded all postautotomy trials within 1-2 days of initiating autotomy, whereas McElroy and Bergmann recorded their trials 14 days post-autotomy. Following autotomy, it is known that body condition declines as resources are diverted towards regeneration (Dial and Fitzpatrick, 1981;Maginnis, 2006;Naya et al, 2007;Wrinn and Uetz, 2007;Fleming et al, 2009;Jagnandan et al, 2014) and could decrease maximum sprint speeds Fleming et al, 2009). In this study, the autotomized tail represented 6-10% of the intact body weight, which could have enabled greater running speeds immediately after tail loss because lizards had less weight to carry.…”
Section: Kinematic Changes Associated With Tail Lossmentioning
confidence: 87%
“…(2) I recorded all postautotomy trials within 1-2 days of initiating autotomy, whereas McElroy and Bergmann recorded their trials 14 days post-autotomy. Following autotomy, it is known that body condition declines as resources are diverted towards regeneration (Dial and Fitzpatrick, 1981;Maginnis, 2006;Naya et al, 2007;Wrinn and Uetz, 2007;Fleming et al, 2009;Jagnandan et al, 2014) and could decrease maximum sprint speeds Fleming et al, 2009). In this study, the autotomized tail represented 6-10% of the intact body weight, which could have enabled greater running speeds immediately after tail loss because lizards had less weight to carry.…”
Section: Kinematic Changes Associated With Tail Lossmentioning
confidence: 87%
“…Decreased stamina may be due to the loss of adipose tissue (fuelling metabolism) in the tail; although we do not know the tissue composition of tails in this species, the tails of these animals are between 9 and 13% of body mass (Medger et al 2008;Fleming et al 2009) and therefore are likely to represent a substantial portion of their body reserves.…”
Section: Introductionmentioning
confidence: 92%
“…has a scansorial pad, similar to those on the feet, which acts as a fifth point of attachment, while the tail itself appears to act as a brace to prevent the animal falling backwards (Bauer & Russell 1994;Medger et al 2008). Fleming et al (2009) reported that autotomized L. capensis incur energetic costs on horizontal surfaces, expending less effort in running, moving both slower and for a shorter distance than intact geckos and having lower excess CO2 production (CO2 production in excess of normal resting metabolic rate) when running.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some lizards, the tail is also an important site for storing lipids, so that in addition to losing mass and having their CoM position shift, animals may also be losing critical energy stores when parts of a tail are lost (e.g. Dial and Fitzpatrick, 1981;Fleming et al, 2009).…”
Section: Introductionmentioning
confidence: 99%